1983
DOI: 10.3109/01913128309141833
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the Liver in the Cerebrohepatorenal Syndrome of Zellweger

Abstract: Three infants with clinical and biochemical features of Zellweger's cerebrohepatorenal syndrome are presented, and the ultrastructural features of successive biopsy and autopsy liver specimens are described. No hepatocellular peroxisomes were found in these patients on routine electron microscopy or electron microscopic histochemistry. In a control group of liver biopsies from 9 patients with other pediatric liver diseases, peroxisomes were readily identifiable in each hepatocyte. Apart from the absence of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 12 publications
3
39
0
Order By: Relevance
“…In particular, peroxisomes seem to be necessary for the maintenance of the integrity of the inner mitochondrial membrane, a finding that confirms previous observations in patients 4,[6][7][8][9] and other mouse models. 13,36,37 Some of the presently observed ultrastructural changes at the inner mitochondrial membrane were similar to the alterations in Zellweger patients.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In particular, peroxisomes seem to be necessary for the maintenance of the integrity of the inner mitochondrial membrane, a finding that confirms previous observations in patients 4,[6][7][8][9] and other mouse models. 13,36,37 Some of the presently observed ultrastructural changes at the inner mitochondrial membrane were similar to the alterations in Zellweger patients.…”
Section: Discussionsupporting
confidence: 79%
“…These changes were highly variable but included alterations at the inner mitochondrial membrane with twisted or irregular cristae, dense matrix and crystalline inclusions, [4][5][6][7][8][9] and a reduction of the activities of complex I and II of the respiratory chain. 10 No abberant mitochondrial morphology was found in other Zellweger patients.…”
mentioning
confidence: 99%
“…Previous studies demonstrated that mitochondria are abnormal in livers of Zellweger patients and mouse Zellweger models [17][18][19][20][21][22][23] and that bile acids may mediate mitochondrial toxicity. 24 Electron microscopy demonstrated mitochondrial abnormalities typically seen in peroxisomal disorders in both early postnatal and P36 untreated PEX2 mutant livers, and these defects persisted in all BA-fed PEX2 Ϫ/Ϫ mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These organelles participate in a number of metabolic cellular processes-e.g., 13-oxidation of fatty acids (11,12), plasmalogen biosynthesis (13,14), and bile acid synthesis (15,16). Peroxisomes are decreased or absent in liver and kidney from patients with the Zellweger cerebrohepatorenal syndrome (17,18), which is characterized biochemically by accumulation ofVLCFA in plasma, tissues, and fibroblasts (19)(20)(21); decreased plasmalogen content of tissues (22,23); and accumulation of pipecolic acid (24,25) and bile acid synthesis intermediates (26)(27)(28) in tissues. The Zellweger syndrome is usually fatal within the first year of life (21), suggesting that peroxisomes play a vital role in normal cellular metabolism.…”
mentioning
confidence: 99%